Galactocele in the Axillary Accessory Breast Mimicking Suspicious Solid Mass on Ultrasound - Donya Farrokh; Ali Alamdaran; Farhad Yousefi; Bita Abbasi (Case Reports in Obstetrics and Gynecology)
Galactoceles are the most common benign breast lesions during breastfeeding period that can mimic carcinomas. We report a galactocele with malignant appearance on ultrasound in the accessory breast. The patient was a 32-year-old lactating woman presented to our hospital for considerable swelling in the left axilla. Ultrasound examination revealed a hypoechoic mass with heterogeneous echogenicity and irregular shape and margins. Sonography-guided aspiration was performed. Aspiration of milky fluid and resolution of the axillary lump after aspiration confirmed the diagnosis of galactocele. Galactocele can present as a suspicious tumoral lesion in the axillary accessory breast and diagnostic aspiration can help in correct diagnosis of this rare lesion in the accessory breast.